Idiopathic normal pressure hydrocephalus, what is the physiotherapist's role in assessment for surgery?. (August 2014) - Gallagher, Ryan; Osmotherly, Peter; Chiarelli, Pauline
Abstract : Background: Idiopathic normal pressure hydrocephalus (iNPH) is a condition resulting in a symptom triad of gait ataxia, cognitive impairment, and urinary incontinence. Idiopathic normal pressure hydrocephalus presents a diagnostic and management dilemma such that management involves the placement of a ventricular peritoneal (VP) shunt to which not all patients will respond. Cerebrospinal fluid (CSF) drainage tests such as the lumbar puncture tap test (TT) provide a prognostic indication of response to shunting. However, determination of what constitutes a positive response to shunting is not clearly defined. While gait improvement following TT has been identified as a possible prognostic indicator, the efficacy of such measures in this clinical population has not been tested. Objectives: To explore the literature related to gait and balance changes associated with iNPH and to identify the possible role physiotherapists might play in the diagnosis of patients with iNPH. Major findings: Gait changes in iNPH patients have been well documented and improvement following TT has been identified as a strong prognostic indicator of improvement following VP shunt insertion. No research has been identified looking directly at balance changes in patients with iNPH following TT or VP shunt insertion and the efficacy of objective gait assessments in this patient population has not been evaluated. No studies have determined the predictability of improvement after shunting based on measured gait improvements following TT. Conclusions: Physiotherapists are expertly placed to be involved in the assessment of symptoms of iNPH. However, further research is required to validate balance and gait assessment in this patient group to determine if prediction of shunt outcome is possible using gait assessment after the TT.